2022
DOI: 10.1002/bies.202100210
|View full text |Cite
|
Sign up to set email alerts
|

A scenario for the origin of life: Volume regulation by bacteriorhodopsin required extremely voltage sensitive Na‐channels and very selective K‐channels

Abstract: The osmotic activity produced by internal, non-permeable, anionic nucleic acids and metabolites causes a persistent and life-threatening cell swelling, or cellular edema, produced by the Gibbs-Donnan effect. This evolutionary-critical osmotic challenge must have been resolved by LUCA or its ancestors, but we lack a cell-physiology look into the biophysical constraints to the solutions. Like mycoplasma, early cells conceivably preserved their volume with Cl − , Na + , and K + -channels, Na + /H + -exchangers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…2) The hydration landscape for each voltage-sensing residue is completely different, implying separate activation trajectories for the voltage sensing arginines or the absence of a unique charge transfer pathway; 3) The VSD is a structurally robust protein domain surrounded by a very malleable lipid and electrostatic environment that retains its structure and function despite mutations in R1-R4, a surprising result given how well conserved R1-R4 are (Gonzalez-Perez et al, 2010;Diaz-Franulic et al, 2018;Naranjo, 2022).…”
Section: 1mentioning
confidence: 99%
“…2) The hydration landscape for each voltage-sensing residue is completely different, implying separate activation trajectories for the voltage sensing arginines or the absence of a unique charge transfer pathway; 3) The VSD is a structurally robust protein domain surrounded by a very malleable lipid and electrostatic environment that retains its structure and function despite mutations in R1-R4, a surprising result given how well conserved R1-R4 are (Gonzalez-Perez et al, 2010;Diaz-Franulic et al, 2018;Naranjo, 2022).…”
Section: 1mentioning
confidence: 99%
“…Moreover, the integration of different physical approaches mentioned above to regulate the dynamic LLPS process has also developed. [80][81][82][83] For instance, Chen et al showed that the dynamic distribution of pLL /ATP coacervate microdroplets within Pickering emulsion-based protocell could be manipulated by changes in temperature or pH. [83] The dynamic spatiotemporal organization of coacervate microdroplets in a protocellular system, on one hand, can be used to explore the nucleation, growth, and dissolution in a defined volume, providing a better understanding of the dynamic LLPS process in a biological system, and on the other hand offers an engineering pathway for organizing different functional units into distinct spatial arrangements in a reversible manner.…”
Section: Dynamic Construction Of Hierarchical Protocellmentioning
confidence: 99%
“…Moreover, the integration of different physical approaches mentioned above to regulate the dynamic LLPS process has also developed. [ 80–83 ] For instance, Chen et al. showed that the dynamic distribution of pLL /ATP coacervate microdroplets within Pickering emulsion‐based protocell could be manipulated by changes in temperature or pH.…”
Section: Intracellular Spatial Organization In Protocellular Systemmentioning
confidence: 99%
“…Such a scenario for the origin of life is explored in David Naranjo's essay on volume regulation by bacteriorhodopsin. [10] The reason is that voltage gated cation channels mediated cation permeation in early cells, because they are one of the largest, diverse, and ancient membrane proteins. The model system presented by Naranjo considers a proto-or early cell in a marine pond in a CO 2rich atmosphere.…”
mentioning
confidence: 99%
“…Such a scenario for the origin of life is explored in David Naranjo's essay on volume regulation by bacteriorhodopsin. [ 10 ]…”
mentioning
confidence: 99%